Investigation on the Quality of Fermented White Yam Flour (Elubo) At Different Drying Temperatures - Ajala, A.S.; Idowu, T.O. (Canadian Journal of Agriculture and Crops, 2016)
Fermented yam flour called „elubo? among „Yorubas? is a product from yam tubers and is one of the most staple foods in West African countries which provide a good source of carbohydrate for people. Knowledge of the anti-nutritional factors and the physicochemical properties of this flour would reduce the detrimental effects on human health and provide information on their end use quality, thereby leading to increased utilization of the flour. In this study, white yam samples were sorted, blanched and dried in the tunnel dryer at a temperature of 50, 60 and 70?. The samples were then cooled, milled, sieved and packaged. The results for moisture, protein, fat, ash, crude fibre and carbohydrate ranged between (7.32 to 10.74) %, (5.19 to 5.32)%, (3.98 to 4.39)%, (3.02 to 3.78)%, (2.69 to 2.82)%, (73.27 to 75.50)% respectively. The result obtained on swelling power, solubility index, bulk density and water absorption capacity ranged from (4.83-5.21) %, (16.71-16.81)%, (1.01-1.15)g/ml and (143.02-151.50)% respectively. The tannin, saponin and phytate content ranged between (0.37-0.42) %, (2.16-2.80)mg/100g and (52.23 to 58.48)mg/kg respectively. The thermal diffusivity, specific heat capacity, thermal conductivity, energy property also ranged from (2.81-2.95) x107 m2/s, (1.62-1.75) kJ/kgk, (0.17-0.21) W/mK and (1497.91 kJ - 1549.68) kJ respectively. The results showed that drying of „elubo? at 70? produced better quality in terms of reduction in moisture content and anti-nutritional factors, high values in functional properties and also high energy values.